Natural Food Security Policy Network for Local Food Development in Bulungan Regency, North Kalimantan Province - Rima Teriyanti; Rulinawaty Kasmad; Entang Adhymuhtar (International Journal Labs, 2025)
This research is motivated by the increasing population that has an impact on increasing the fulfillment of food needs and the threat of food insecurity in the long term and currently Indonesia is experiencing economic turmoil, increasing global population, and climate change causing an increase in the price of major commodities. Bulungan Regency has a good and Very Resilient Food Security Index reaching 77.11 in 2023 and 77.00 in 2022, an increase that is not yet significant, this is because there are still problems including the amount of food demand that is higher than the amount of supply, the difficulty of availability of local food use, lack of coordination and communication to the community level, the use of local-based wheat flour can only be found in remote areas, minimal data and slow data collection processes, and the difficulty of aligning perceptions regarding the identification of assessment indicators to formulate data. The author's purpose in this study is to analyze the Food Security Policy Network in local food development and strategies that must be carried out in improving local food development in Bulungan Regency. This type of research is Descriptive with a Qualitative approach and researchers as research instruments. Data collection techniques by interviews, observation, and documentation. Data analysis was carried out by data reduction, data presentation, and conclusion drawing. The results of the study show that from the contact aspect, a formal organizational structure and division of tasks have been formed but still tend to be sectoral and have not shown consistent coordination, from the trust aspect, the entire FSVA Team has been formed, but has not fully reached grassroots actors such as farmers and MSMEs, from the information sharing aspect, the existence of food security data through FSVA documents has become an important source of information, but its distribution and utilization are still limited, from the aspect of resource exchange, limited human resources, agricultural infrastructure, and local institutional involvement are still obstacles in optimizing policies. The conclusion of the study shows that the Governance Network in Food Security Policy in Local Food Development in Bulungan Regency has been running with the formation of the FSVA Team but still needs strengthening in the aspect of cross-sector coordination, building more equitable trust, a more effective information dissemination system, and integration and optimization of the use of local resources.